1982
DOI: 10.1159/000250089
|View full text |Cite
|
Sign up to set email alerts
|

Localized Pustular Vasculitis in Rheumatoid Arthritis

Abstract: This report describes a case of sterile pustulosis accompanied by underlying leukocytoclastic vasculitis which occurred in the absence of apparent infection or drug allergy on the lower legs of a 46-year-old housewife with 10 years’ duration of rheumatoid arthritis. Histamine-induced vascular changes studied by immunofluorescence microscopy demonstrated a perivascular C3 deposition suggesting the presence of immune complexes. We speculate that some unknown triggers have induced trapping circulating immune comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…These signs can be seen in many differ ent conditions such as acute generalized pustular bacterid, Behcet's syndrome, bowel-bypass syndrome and dissem inated gonococcal infection. Additionally Miyachi et al [3] reported localized pustular vasculitis in a patient with rheu matoid vasculitis. Histologically their case showed a spon giform pustule with underlying lcukocytoclastic vasculitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These signs can be seen in many differ ent conditions such as acute generalized pustular bacterid, Behcet's syndrome, bowel-bypass syndrome and dissem inated gonococcal infection. Additionally Miyachi et al [3] reported localized pustular vasculitis in a patient with rheu matoid vasculitis. Histologically their case showed a spon giform pustule with underlying lcukocytoclastic vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Pustular vasculitis is a disease concept that results from a heterogeneous group of disorders character ized by clinically cutaneous pustules on purpuric bases and histologically a neutrophilic vasculitis [1]. These findings may be found in patients with acute generalized pustular bacterid, Behcet's syndrome, bowel-associated dermatosisarthritis syndrome or disseminated gonococcal infection [1][2][3]. Recently we experienced an unique case of pustular vasculitis with a clinical feature similar to those seen in both pustular psoriasis and pustular bacterid.…”
mentioning
confidence: 99%
“…In rice, there are 9 canonical casein kinase 1 and 6 plant specific casein kinase 1 [ 13 ]. Both two types of CKI family have important functions in the regulation of a variety of biological processes related to growth and development, as well as various responses to environmental stimuli [ 14 ]. In rice, abscisic acid (ABA) and brassinolide caused up-regulation of OsCKI1 (canonical casein kinase 1), while OsCKI1 deficiency caused shorter primary roots and fewer lateral and adventitious roots [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A case of localized pustular vasculitis in RA has recently been reported. The authors suggested that immune complexes may play a role in the pathogenesis of pustular vasculi tis (6).…”
mentioning
confidence: 99%